2020
DOI: 10.1371/journal.pone.0228482
|View full text |Cite
|
Sign up to set email alerts
|

Child handwashing in an internally displaced persons camp in Northern Iraq: A qualitative multi-method exploration of motivational drivers and other handwashing determinants

Abstract: Background Children in humanitarian situations are particularly vulnerable to diseases such as diarrhoea. Handwashing with soap can greatly reduce transmission but handwashing rates are often low and traditional interventions ineffective. To aid future intervention design, this study aims to understand the determinants of child handwashing and the key motivational drivers of children's behaviour within a specific humanitarian setting. Methods In an internally displaced persons camp in Northern Iraq we conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Moreover, handwashing frameworks have been criticized for their bias towards certain sets of determinants (e.g., individual-level or structural determinants) because they risk missing its complexity [ 17 ]. In contrast, socioecological frameworks allow for the conceptualization of multi-level determinants of handwashing and have shown the high relevance of social- and structural-level factors in addition to individual factors [ 58 , 59 ]. However, they do not explicitly take into account power gradients and differing degrees of vulnerability between groups in a shared social setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, handwashing frameworks have been criticized for their bias towards certain sets of determinants (e.g., individual-level or structural determinants) because they risk missing its complexity [ 17 ]. In contrast, socioecological frameworks allow for the conceptualization of multi-level determinants of handwashing and have shown the high relevance of social- and structural-level factors in addition to individual factors [ 58 , 59 ]. However, they do not explicitly take into account power gradients and differing degrees of vulnerability between groups in a shared social setting.…”
Section: Discussionmentioning
confidence: 99%
“…Actual or perceived scarcities of water and soap and the de-prioritisation of these items for handwashing (as opposed to other household tasks) have been identified as common challenges in the wake of humanitarian crises [ 49 52 ]. The availability of desirable and conveniently located handwashing facilities is thought to be one of the most influential determinants of hygiene behaviour in stable settings [ 7 , 12 , 53 ] and improving handwashing infrastructure may have an even greater influence among displaced populations [ 51 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found handwashing was most strongly influenced by motives of disgust, status and comfort. Other studies among displaced populations have suggested motives of nurture and affiliation should be utilised by hygiene programmes in humanitarian settings [ 51 , 56 , 57 ]. The use of emotional drivers in hygiene programming remains contentious.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we identified no respiratory hygiene intervention studies in humanitarian contexts. [14][15][16] Humanitarian context hand hygiene studies report that information is necessary-but not sufficient-to motivate hand hygiene [17][18][19] and call for behaviour change strategies. 18 No adolescent/youth hand hygiene studies were located in humanitarian contexts.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…A study with internally displaced children in Iraq identified hand hygiene determinants included hygiene promotion, social norms and motivational drivers. 19 A hand hygiene study with displaced adults in the Democratic Republic of Congo highlighted the role of emotional and social motivators and a need for innovation. 20 Physical distancing is not feasible in crowded settlements, 21 yet limited research has assessed strategies to promote alternatives such as household or community shielding.…”
Section: Introductionmentioning
confidence: 99%